2002
DOI: 10.4269/ajtmh.2002.67.597
|View full text |Cite
|
Sign up to set email alerts
|

Low antibody responses to variant surface antigens of Plasmodium falciparum are associated with severe malaria and increased susceptibility to malaria attacks in Gabonese children.

Abstract: Abstract:We measured the levels of IgG antibodies with specificity for the variant surface antigens (VSA) of Plasmodium falciparum in plasma samples from a cohort of Gabonese children participating in a longitudinal casecontrol malaria study. Children with mild malaria had significantly higher anti-VSA IgG responses than their matched counterparts with severe malaria, most markedly during convalescence and when they were healthy. Over the course of the study, almost twice as many children who presented initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 46 publications
(62 reference statements)
3
29
2
Order By: Relevance
“…We were therefore interested to know whether African children exposed to intense and perennial transmission of P. falciparum exhibit a similar isotypic profile of anti-VSA IgG antibodies. Data from a small-scale Kenyan study have, in addition, suggested that children who are susceptible to severe malaria may display altered dynamics of anti-VSA antibody responses, which is in accord with our own recent report (5,36). Here we addressed this question further through comparison of the IgG isotype profiles of anti-VSA antibodies in Gabonese children with differing outcomes of infection in terms of the clinical severity of P. falciparum malaria.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…We were therefore interested to know whether African children exposed to intense and perennial transmission of P. falciparum exhibit a similar isotypic profile of anti-VSA IgG antibodies. Data from a small-scale Kenyan study have, in addition, suggested that children who are susceptible to severe malaria may display altered dynamics of anti-VSA antibody responses, which is in accord with our own recent report (5,36). Here we addressed this question further through comparison of the IgG isotype profiles of anti-VSA antibodies in Gabonese children with differing outcomes of infection in terms of the clinical severity of P. falciparum malaria.…”
supporting
confidence: 75%
“…This represents persuasive evidence for a protective function of antibodies of the major cytophilic IgG isotype directed to the VSA expressed by heterologous parasite isolates of a particular subtype. Such infection-induced cytophilic antibodies could mediate their effects via targeting of determinants expressed by P. falciparum VSA, leading to blockade of infected erythrocyte cytoadherence to endothelial cells, and/or opsonization, leading to phagocytosis through interactions with Fc␥ receptors on phagocytic cells (36). The putative principal target of anti-VSA antibodies, PfEMP-1, is known to contain conserved epitopes that are recognized by antibodies from African children and adults (11,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that parasites causing severe malaria in young children express a limited set of PfEMP1s on the surface of the infected erythrocytes and that children acquire protection from severe noncerebral malaria early in life (14) because antibodies against these parasite forms are acquired after the first infections (4,30,39). These results imply that the host environment shapes PfEMP1 expression by parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Variant surface antigens (VSA) appear to play a major role in malaria pathogenesis and to be key targets for acquired immunity (10,13,17,46). Moreover, severe disease in children is associated with parasites expressing a restricted subset of VSA (VSA SM ), and children possessing antibodies against these antigenic types seem to be protected against severe, noncerebral malaria (7,32,33).…”
mentioning
confidence: 99%